Electromagnetic transient parallel simulation optimisation based on GPU - Shujun Yao (The Journal of Engineering, 2019)
The development of smart grid and the increasing scale of power system bring much pressure to the electromagnetic transient simulation of a power system. The graphic processing unit (GPU), which features the massive concurrent threads and excellent floating point performance, brings a new chance to the area of power system simulation. This study introduces a parallel lower triangular and upper triangular decomposition algorithm and calculation strategy of electromagnetic transient simulation based on GPU. In this scheme, the GPU is mainly used to do the computationally intensive part of the simulation in parallel on its built-in multiple processing cores, and the CPU is assigned for updating history terms and flow control of the simulation. By comparing with the results simulating by the CPU-only implementations, the validity and efficiency of the proposed method are verified.